Audience Segmentation of Kentucky Mothers by Nonparticipation Status in the Special Supplemental Nutrition Program for Women, Infants, and Children. Issue 1 (2nd January 2017) - Panzera, Anthony D.; Bryant, Carol A.; Hawkins, Fran; Goff, Rhonda; Napier, Ashley; Kirby, Russell S.; Coulter, Martha L.; Sappenfield, William M.; Baldwine, Julie; O'Rourke, Kathleen
ABSTRACT: We identify women most and least likely to discontinue participation in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) program. Kentucky WIC program management information system data from 2012 to 2013 was explored through a retrospective cohort study. Audience segmentation identified unique groups with respect to nonparticipation. Presumptive eligibility for Medicaid was the strongest predictor of nonparticipation. Among those who were not presumptively eligible, women who were the only ones in their households enrolled in the program were at higher risk of nonparticipation. Outreach strategies at the point of enrollment or when presumptive eligibility for Medicaid is granted could mitigate further nonparticipation.